Maternal pesticide exposure and risk of birth defects: a population-based cross-sectional study in China - Liu, Fangfang; Li, Xiayang; Chen, Jie; Huang, Yishuai; Dang, Shaonong (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to examine the association between maternal pesticide exposure during the periconceptional period and birth defects in their offspring.MethodsA survey was conducted among 29,204 women with infants born between 2010 and 2013 in Shaanxi Province, Northwest China. All cases of birth defects were diagnosed using the International Classification of Diseases, Tenth Revision (ICD-10). Given the multistage sampling design, the generalized estimating equation (GEE) binomial regression models with log link and exchangeable correlation structures were used to analyze the association between maternal pesticide exposures and birth defects.ResultsAmong the 29,204 subjects, 562 mothers had children with birth defects, resulting in an incidence rate of 192.44 per 10,000 live births. The incidence of birth defects was higher in the pesticide-exposed group compared to the control group (737.46/10,000 vs. 186.04/10,000). After adjusting for baseline demographic characteristics, fertility status, nutritional factors, and environmental factors in the GEE model, the results indicated that the risk of birth defects and cardiovascular system defects in mothers exposed to pesticides during the periconceptional period was 2.39 times (95% CI: 1.84–3.10) and 3.14 times (95% CI: 1.73–5.71) higher, respectively, compared to the control group.ConclusionThis study demonstrated that maternal exposure to pesticides during the periconceptional period was associated with an increased risk of birth defects, particularly cardiovascular system defects in offspring. Consequently, it would be beneficial to avoid pesticide exposure from three months before pregnancy through the first trimester to lower birth defects in infants.